Manufacturing method of electrode member
Patent Information
- Application Number
- JP2022557603
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-23
- Filing Date
- 2021-10-21
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-10-21
AI Technical Summary
【0018】 また、ここに開示される製造方法の一態様において、電極部材は、固体電解質粒子を含む固体電解質層であり、成形工程において箔状の基材の表面に合材スラリーを塗布し、乾燥工程後に得た成形体から箔状の基材を剥がす。ここに開示される製造方法によると、全固体電池の固体電解質層を製造することもできる。かかる固体電解質層を製造する場合には、箔状の基材の表面に合材スラリーを塗布し、乾燥させた合材スラリーから基材を剥がすことが好ましい。これによって、固体電解質層を効率よく、容易に製造できる。
Smart Images

Figure 0007609883000004 
Figure 0007609883000005 
Figure 0007609883000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing an electrode member. More specifically, the present invention relates to a method for manufacturing an electrode member constituting an electrode body of an all-solid-state battery. This international application claims priority based on Japanese Patent Application No. 2020-177685 filed on October 23, 2020, the entire contents of which are incorporated herein by reference. [Background technology]
[0002] Secondary batteries such as lithium ion secondary batteries are widely used in fields such as portable power sources for personal computers and mobile terminals, and power sources for driving vehicles such as electric vehicles (EVs), hybrid vehicles (HVs), and plug-in hybrid vehicles (PHVs). Such secondary batteries usually include a positive electrode, a negative electrode, and an electrolyte. One example of such a secondary battery is a liquid battery that uses an electrolytic solution as the electrolyte. Another example is an all-solid-state battery that uses a solid electrolyte as the electrolyte.
[0003] Moreover, the electrodes (positive and negative electrodes) of a secondary battery are prepared, for example, by applying a composite slurry made by kneading predetermined materials onto the surface of a current collector foil and drying it. A binder is added to this composite slurry to bind granular materials such as active materials together. A polymer that can be dissolved or dispersed in the solvent of the composite slurry is used as the binder. For example, when the solvent of the composite slurry is aqueous, styrene butadiene rubber (SBR) or the like is used as the binder. On the other hand, when the solvent is non-aqueous, polyvinylidene fluoride (PVdF) or the like is used. It is also known that the function of these binders is affected by temperature. For example, Patent Documents 1 to 3 disclose a technique for controlling the temperature of the composite slurry in order to properly exert the function of the binder in a liquid battery. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 10-284052 [Patent Document 2] Japanese Patent Application Publication No. 2017-188397 [Patent Document 3] Japanese Patent Application Publication No. 2004-247180 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been an increasing demand for practical use of all-solid-state batteries from the viewpoints of improving safety and miniaturization. In such all-solid-state batteries, unlike liquid-based batteries, a solid electrolyte layer containing solid electrolyte particles is disposed between the positive electrode and the negative electrode. This solid electrolyte layer not only serves as an electrolyte in liquid-based batteries, but also serves as a separator. Another feature of all-solid-state batteries is that solid electrolyte particles are added not only to the solid electrolyte layer but also to the positive electrode and the negative electrode. The solid electrolyte layer of the all-solid-state battery is produced by forming a composite slurry containing solid electrolyte particles and a binder into a desired shape and then drying it, similar to the positive electrode and the negative electrode.
[0006] However, in the manufacture of all-solid-state batteries, unlike the manufacture of liquid batteries, the composite slurry may gel during the preparation of the positive electrode, negative electrode, and solid electrolyte layer (hereinafter collectively referred to as "electrode members"). The viscosity of the gelled composite slurry increases rapidly, making it difficult to mold it into a desired shape. In addition, since granular materials such as active materials and solid electrolyte particles are unevenly distributed in the gelled slurry, the battery resistance may increase significantly when the electrode member is prepared using the slurry.
[0007] The present invention has been made in view of the above problems, and has an object to prevent gelation of a composite slurry at least until the start of a molding step in the production of an electrode member for an all-solid-state battery. [Means for solving the problem]
[0008] The present inventors conducted experiments and studies to solve the above-mentioned problems, and found the cause of gelation of the composite slurry in the manufacturing of the electrode member of the all-solid-state battery. Specifically, unlike liquid-based batteries, the electrode members (positive electrode, negative electrode, and solid electrolyte layer) of the all-solid-state battery contain solid electrolyte particles. For this reason, in the preparation of the composite slurry, it is necessary to use a low-polarity nonaqueous solvent that has low reactivity with the solid electrolyte particles. However, this low-polarity nonaqueous solvent has a property that the crystalline component of the binder once dissolved is easily recrystallized because of low solubility of the binder. And, the viscosity of the recrystallized binder increases rapidly, so there is a risk of gelling the composite slurry. Based on this knowledge, the present inventors thought that if the crystalline component of the binder dissolved in the solvent can be prevented from recrystallizing in the manufacturing process of the electrode member of the all-solid-state battery, the gelation of the composite slurry can be prevented. The manufacturing method of the electrode member disclosed herein (hereinafter, also simply referred to as the "manufacturing method") was made based on this knowledge.
[0009] The manufacturing method disclosed herein includes at least a slurry preparation step of preparing a composite slurry containing a binder, solid electrolyte particles, and a low-polarity nonaqueous solvent, a molding step of molding the composite slurry into a desired shape, and a drying step of removing the low-polarity nonaqueous solvent from the molded composite slurry to obtain a molded body. The manufacturing method disclosed herein is characterized in that the temperature of the composite slurry is controlled so that recrystallization of the binder dissolved in the low-polarity nonaqueous solvent does not occur at least until the molding step is started.
[0010] In the manufacturing method having such a configuration, the temperature of the composite slurry is controlled so that the crystalline components of the binder dissolved in the solvent do not recrystallize, and therefore gelation of the composite slurry can be prevented. In addition, in this manufacturing method, gelation of the composite slurry is prevented at least until the molding process is started, and therefore it is possible to suitably prevent a decrease in manufacturing efficiency due to a sudden increase in viscosity, an increase in battery resistance due to uneven distribution of the granular material, and the like.
[0011] In a preferred embodiment of the manufacturing method disclosed herein, the binder is polyvinylidene fluoride (PVdF). PVdF has the advantage of being suitable as a binder for use in electrode members of all-solid-state batteries due to its high voltage resistance and low reactivity with solid electrolyte particles, but it also has the disadvantage of being prone to gelling of the composite slurry due to recrystallization due to its particularly low solubility in low-polarity nonaqueous solvents. In contrast, the manufacturing method disclosed herein can prevent gelling of the composite slurry due to recrystallization of the binder, eliminating the disadvantages of using PVdF as a binder and allowing only the advantages to be enjoyed.
[0012] In an embodiment in which PVdF is used as the binder, the PVdF is preferably PVdF-HFP, which is a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP). PVdF-HFP has a relatively high solubility in low-polarity non-aqueous solvents, and therefore can more effectively prevent recrystallization of the dissolved binder.
[0013] In a preferred embodiment of the manufacturing method disclosed herein, the melting start temperature of the binder is T m The maximum temperature of the mixture slurry is T max When the temperature of the composite slurry is controlled so as to satisfy the following formula (1) at least until the molding step is started. T max ≦T m (1) In this embodiment, the maximum temperature T of the composite slurry is maintained at least until the molding process is started. max is the binder melting temperature T m Below (T max ≦T m This prevents the crystalline components of the binder from dissolving, and therefore makes it possible to effectively prevent the mixture slurry from gelling due to recrystallization of the binder once dissolved.
[0014] In the embodiment in which the temperature of the composite slurry is controlled to satisfy the above formula (1), the maximum temperature T maxis the binder melting temperature T m It is preferable that the temperature is at least 5° C. lower than the temperature at which the binder is heated. This can reliably prevent the crystalline components of the binder from dissolving.
[0015] In a preferred embodiment of the manufacturing method disclosed herein, the melting start temperature of the binder is T m and the recrystallization temperature of the binder is T c The boiling point of the low polarity non-aqueous solvent is T b The maximum temperature of the mixture slurry is T max The minimum temperature of the mixture slurry is T min When the temperature of the composite slurry is set at 100° C., the temperature of the composite slurry is controlled so as to satisfy the following formulas (2) and (3) at least until the molding step is started. T m <T max <T b (2) T min ≧T c (3) In this embodiment, the maximum temperature T max is the binder melting temperature T m (T m <T max ), the crystalline components of the binder dissolve in the low-polarity nonaqueous solvent. However, in this embodiment, the minimum temperature T min is the recrystallization temperature T c That's all (T min ≧T c ), the crystalline components of the binder can be kept dissolved in the solvent. This effectively prevents the mixture slurry from gelling due to recrystallization of the binder. max The boiling point T of the low polarity non-aqueous solvent becomes too high. b If the maximum temperature T of the composite slurry is exceeded, the low-polarity nonaqueous solvent may evaporate and the viscosity of the composite slurry may increase rapidly. max is the boiling point T of the low polarity non-aqueous solvent b is controlled below (T max <T b ).
[0016] In the embodiment in which the temperature of the composite slurry is controlled to satisfy the above formulas (2) and (3), the minimum temperature T min is the recrystallization temperature T c This ensures that the crystalline components of the binder remain dissolved in the solvent.
[0017] In one aspect of the manufacturing method disclosed herein, a composite layer containing solid electrolyte particles and an electrode active material is formed on the surface of a current collector foil to form a positive electrode or a negative electrode, and a composite slurry is applied to the surface of the current collector foil in a molding step. The manufacturing method disclosed herein can manufacture positive electrodes and negative electrodes of all-solid-state batteries. When manufacturing these electrodes, the manufacturing efficiency can be improved by adopting a molding step in which the composite slurry is applied to the surface of the current collector foil.
[0018] In one embodiment of the manufacturing method disclosed herein, the electrode member is a solid electrolyte layer containing solid electrolyte particles, and in the molding step, a composite slurry is applied to the surface of a foil-shaped substrate, and the foil-shaped substrate is peeled off from the molded body obtained after the drying step. According to the manufacturing method disclosed herein, a solid electrolyte layer of an all-solid-state battery can also be manufactured. When manufacturing such a solid electrolyte layer, it is preferable to apply a composite slurry to the surface of a foil-shaped substrate, and peel off the substrate from the dried composite slurry. This allows the solid electrolyte layer to be manufactured efficiently and easily. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a plan view illustrating a schematic diagram of an example of an all-solid-state battery. [Diagram 2] FIG. 2 is a cross-sectional view taken along line II-II in FIG. [Diagram 3] FIG. 3 is a flow diagram showing the method for producing the all-solid-state battery disclosed herein. [Figure 4] FIG. 4 is a graph showing the measurement results of the viscosity increase rates of Samples 1-18. [Diagram 5]FIG. 5 is a graph showing the measurement results of the battery resistance of Samples 1-18. [Figure 6] FIG. 6 is a graph showing the measurement results of the viscosity increase rates of Samples 19 to 36. [Figure 7] FIG. 7 is a graph showing the measurement results of the battery resistance of Samples 19-36. [Figure 8] FIG. 8 is a graph showing the measurement results of the viscosity increase rates of Samples 37 to 48. [Figure 9] FIG. 9 is a graph showing the measurement results of the battery resistance of Samples 37-48. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the technology disclosed herein will be described. Note that the embodiment described below is not intended to limit the technology disclosed herein. Furthermore, matters other than those specifically mentioned in this specification and necessary for implementing the technology disclosed herein (for example, the detailed configuration of the device (applicator, etc.) used in manufacturing the electrode member) can be understood as design matters of a person skilled in the art based on the conventional technology in the field. The technology disclosed here can be implemented based on the contents disclosed in this specification and the technical common sense in the field. Furthermore, when a numerical range is described as A to B (where A and B are arbitrary numerical values) in this specification, it means A or more and B or less.
[0021] 1. Structure of all-solid-state batteries In this specification, for convenience of explanation, the structure of the all-solid-state battery will be described first. Note that the structure of the all-solid-state battery described below is not intended to limit the manufacturing method of the electrode member disclosed herein.
[0022] (1) Overall structure Fig. 1 is a plan view showing a schematic diagram of an example of an all-solid-state battery. Fig. 2 is a cross-sectional view taken along the line II-II in Fig. 1. In the drawing, the symbol X indicates the "width direction (of the all-solid-state battery)", the symbol Y indicates the "depth direction (of the all-solid-state battery)", and the symbol Z indicates the "height direction (of the all-solid-state battery)". However, these directions are determined for the convenience of explanation, and are not intended to limit the installation mode when using the all-solid-state battery.
[0023] As shown in Fig. 1, this all-solid-state battery 1 includes an electrode body 10 and an exterior body 20 that houses the electrode body 10. Specifically, a pair of laminate films are opposed to each other with the electrode body 10 sandwiched therebetween, and the outer peripheries of the laminate films are welded. This forms the exterior body 20 with a welded portion 22 formed on the outer periphery, and houses the electrode body 10 inside.
[0024] A positive electrode terminal 30 is provided on one side edge in the width direction X of the all-solid-state battery 1 (left side in FIG. 1). One end of the positive electrode terminal 30 is connected to the electrode body 10 inside the exterior body 20, and the other end is exposed to the outside of the exterior body 20. The positive electrode terminal 30 is made of aluminum or the like. A negative electrode terminal 40 is provided on the other side edge in the width direction X of the all-solid-state battery 1 (right side in FIG. 1). Like the positive electrode terminal 30, one end of the negative electrode terminal 40 is connected to the electrode body 10, and the other end is exposed to the outside of the exterior body 20. The negative electrode terminal 40 is made of copper or the like.
[0025] As shown in Fig. 2, the electrode body 10 is constructed by sequentially laminating a plurality of sheet materials each consisting of a positive electrode 50, a negative electrode 60, and a solid electrolyte layer 70. In this specification, the sheet materials constituting the electrode body 10 are collectively referred to as "electrode members." That is, in this specification, "electrode members" is a general term for the constituent materials of the electrode body, and includes the positive electrode, the negative electrode, and the solid electrolyte layer. Each electrode member will be described below.
[0026] (1) Positive electrode The positive electrode 50 includes a positive electrode current collector foil 52 and a positive electrode composite layer 54 formed on the surfaces (both surfaces) of the positive electrode current collector foil 52. The positive electrode current collector foil 52 is preferably made of a conductive material such as aluminum or an aluminum alloy. The positive electrode current collector foil 52 is electrically connected to the above-mentioned positive electrode terminal 30 (see FIG. 1). On the other hand, the positive electrode composite layer 54 contains a positive electrode active material, solid electrolyte particles, and a binder.
[0027] The positive electrode active material is a material capable of reversibly absorbing and releasing charge carriers (e.g., lithium ions). Any material that can be used in this type of secondary battery can be used as the positive electrode active material without any particular limitation. Examples of such positive electrode active materials include lithium transition metal composite oxides such as lithium nickel-containing composite oxides, lithium cobalt-containing composite oxides, lithium nickel cobalt-containing composite oxides, lithium manganese-containing composite oxides, and lithium nickel cobalt manganese-containing composite oxides.
[0028] The solid electrolyte particles are granular solid electrolytes. Note that the solid electrolyte particles contained in the positive electrode mixture layer 54 can be made of the same material as that used in the solid electrolyte layer 70 described later, and therefore detailed description thereof will be omitted here.
[0029] The binder bonds the granular materials (such as the positive electrode active material and the solid electrolyte particles) in the positive electrode mixture layer 54 together, improving the moldability of the positive electrode mixture layer 54. For the binder of the all-solid-state battery 1, it is preferable to select a polymer that has high voltage resistance and low reactivity with the solid electrolyte particles. From this viewpoint, examples of the polymer include polyvinylidene fluoride (PVdF), polyvinylidene chloride (PVdC), polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), ethylene tetrafluoroethylene polymer (ETFE), ethylene chlorotrifluoroethylene copolymer (ECTFE), and the like. In addition, as will be described later in detail, in the manufacture of the all-solid-state battery 1, a low-polarity non-aqueous solvent is used as the solvent for the mixture slurry from the viewpoint of preventing reaction with the solid electrolyte particles. If the affinity (solubility and dispersibility) of the binder for such a low-polarity non-aqueous solvent becomes too low, it may become difficult to control the temperature of the mixture slurry, which will be described later. From this viewpoint, it is preferable that the binder has excellent affinity for the low-polarity non-aqueous solvent. An example of such a binder is a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP) (PVdF-HFP).
[0030] The positive electrode mixture layer 54 may contain additives other than the above-mentioned materials. As the other additives, any conventionally known materials that can be added to the positive electrode mixture layer of a secondary battery can be used as long as they do not impair the effects of the technology disclosed herein. An example of the additive is a conductive material. Examples of the conductive material include acetylene black and vapor grown carbon fiber (VGCF).
[0031] (2) Negative electrode The negative electrode 60 includes a negative electrode current collector foil 62 and a negative electrode composite layer 64 provided on the surface (both sides) of the negative electrode current collector foil 62. The negative electrode current collector foil 62 is preferably made of a conductive material such as copper or a copper alloy. The negative electrode current collector foil 62 is electrically connected to the negative electrode terminal 40 (see FIG. 1). On the other hand, the negative electrode composite layer 64 includes a negative electrode active material, solid electrolyte particles, and a binder. The negative electrode active material is a material capable of reversibly absorbing and releasing charge carriers (e.g., lithium ions). The negative electrode active material can be any material that can be used in this type of secondary battery without any particular restrictions. Examples of such negative electrode active materials include carbon materials such as hard carbon, graphite, and boron-added carbon. The binder and solid electrolyte particles can be made of the same materials as those of the positive electrode composite layer 54, so that a duplicated description will be omitted. The negative electrode mixture layer 64 may contain materials other than the negative electrode active material, binder, and solid electrolyte particles (e.g., conductive materials, thickeners, etc.). As for the additives, conventionally known materials that can be added to the negative electrode mixture layer of a secondary battery can be used as long as they do not impair the effects of the technology disclosed herein.
[0032] (3) Solid electrolyte layer The solid electrolyte layer 70 is disposed between the positive electrode 50 and the negative electrode 60. The solid electrolyte layer 70 functions as an electrolyte that conducts charge carriers (e.g., Li ions) between the positive electrode 50 and the negative electrode 60, and as a separator that insulates the positive electrode 50 and the negative electrode 60. The solid electrolyte layer 70 contains solid electrolyte particles and a binder. Note that the binder can be made of the same material as the positive electrode mixture layer 54 and the negative electrode mixture layer 54, and therefore a duplicated description will be omitted.
[0033] On the other hand, for the solid electrolyte particles, sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, halide solid electrolytes, etc. are used. Among these solid electrolytes, sulfide solid electrolytes are preferred from the viewpoint of excellent ion conductivity. Examples of such sulfide solid electrolytes include Li2S-SiS2-based materials, Li2S-P2S3-based materials, Li2S-P2S5-based materials, Li2S-GeS2-based materials, Li2S-B2S3-based materials, Li3PO4-P2S5-based materials, Li4SiO4-Li2S-SiS2-based materials, etc. In addition, from the viewpoint of realizing higher ion conductivity, the sulfide solid electrolyte may be a Li2S-based solid solution composed of Li2S and lithium halide (e.g., LiCl, LiBr, LiI). Suitable examples of such sulfide solid electrolytes include LiBr-Li2S-P2S5, LiI-Li2S-P2S5, LiBr-LiI-Li2S-P2S5, etc.
[0034] As described above, the electrode materials (positive electrode 50, negative electrode 60, and solid electrolyte layer 70) constituting the electrode body 10 of the all-solid-state battery 1 have in common the fact that they are provided with a layer containing solid electrolyte particles and a binder. According to the manufacturing method disclosed herein, it is possible to manufacture an electrode member containing such a binder and solid electrolyte particles. In other words, the manufacturing method disclosed herein can be applied to the manufacture of any of the positive electrode, negative electrode, and solid electrolyte layer.
[0035] 2. Manufacturing method of electrode components Next, the manufacturing method of the electrode member disclosed herein will be described. Fig. 3 is a flow chart showing the manufacturing method of the electrode member disclosed herein. As shown in Fig. 3, the manufacturing method disclosed herein includes a slurry preparation step S10, a molding step S20, and a drying step S30. Each step will be described below.
[0036] (1) Slurry preparation process S10 In this process, a composite slurry containing at least a binder, solid electrolyte particles, and a low-polarity non-aqueous solvent is prepared. The components of the composite slurry can be appropriately adjusted depending on the type of electrode member to be manufactured. For example, when the object to be manufactured is a positive electrode, a positive electrode active material is added in addition to the binder, solid electrolyte particles, and low-polarity non-aqueous solvent. When a negative electrode is manufactured, a negative electrode active material is added in addition to the binder, solid electrolyte particles, and low-polarity non-aqueous solvent. When a solid electrolyte layer is manufactured, the binder, solid electrolyte particles, and low-polarity non-aqueous solvent are mixed without adding an electrode active material. Note that each material (binder, solid electrolyte particles, positive electrode active material, negative electrode active material, etc.) has already been described, so duplicated description will be omitted.
[0037] In the manufacturing method disclosed herein, a low-polarity nonaqueous solvent is used as the solvent for the composite slurry. In a typical secondary battery, a high-polarity nonaqueous solvent such as N-methylpyrrolidone (NMP) is used as the solvent for the composite slurry from the viewpoint of affinity with the binder. However, the high-polarity nonaqueous solvent may react with the solid electrolyte particles and greatly reduce the ion conductivity. For this reason, in an all-solid-state battery, it is necessary to use a low-polarity nonaqueous solvent that is less reactive with the solid electrolyte particles. However, this low-polarity nonaqueous solvent has a low affinity with the binder and is prone to recrystallization of the binder once dissolved, which may cause the composite slurry to gel. As will be described in detail later, in the manufacturing method disclosed herein, the temperature of the composite slurry is controlled so that the composite slurry does not gel even when such a low-polarity nonaqueous solvent is used. Examples of low polarity non-aqueous solvents include butyl butyrate, heptane, methyl isocyanate, benzyl butyl phthalate, ε-caprolactam, methyl isobutyl ketone, diisobutyl ketone, ρ-xylene, and anisole.
[0038] In addition, in this step, a kneading process is carried out using a conventionally known stirring / mixing device. Examples of such stirring / mixing devices include a ball mill, a roll mill, a mixer, a disperser, a kneader, and an ultrasonic homogenizer. In addition, it is preferable to appropriately adjust the kneading time from the viewpoint of uniformly dispersing each component. Although it may vary depending on the components to be added and the device to be used, as an example, the kneading time is preferably 2 minutes or more, more preferably 3 minutes or more, even more preferably 4 minutes or more, and particularly preferably 5 minutes or more. On the other hand, from the viewpoint of maintaining a suitable production efficiency, the kneading time is preferably 45 minutes or less, more preferably 35 minutes or less, even more preferably 25 minutes or less, and particularly preferably 20 minutes or less.
[0039] (2) Molding process S20 In the forming step S20, the composite slurry is formed into a desired shape. For example, when the manufacturing object (electrode member) is a positive electrode 50 or a negative electrode 60, it is preferable to apply the composite slurry to the surface of the current collector foil in this step. This allows the composite slurry to be formed into a layer and applied to the current collector foil, making it possible to efficiently manufacture the electrode. Note that it is preferable to use an applicator, a die coater, or the like to apply the composite slurry.
[0040] On the other hand, unlike the positive electrode 50 and the negative electrode 60, the solid electrolyte layer 70 is not a member to which a current collector foil is attached. When manufacturing such a solid electrolyte layer 70, it is preferable to apply the composite slurry to the surface of a foil-shaped substrate in the molding step S20, and peel off the substrate from the molded body (the dried composite slurry) after the drying step S30 described later. This makes it possible to easily manufacture the solid electrolyte layer 70 in a desired shape. Furthermore, when manufacturing the solid electrolyte layer 70, it is not necessary to use the foil-shaped substrate as described above. For example, the composite slurry can be molded into a layer shape by using an extrusion molding machine or the like, so that the solid electrolyte layer 70 can be manufactured without using a substrate.
[0041] (3) Drying process S30 In this step, the low polarity non-aqueous solvent is removed from the composite slurry after the molding step. Typically, in this step, the low polarity non-aqueous solvent is removed at a temperature below the boiling point Tb The composite slurry is heated at a temperature exceeding 200° C. As a result, the low-polarity nonaqueous solvent is removed from the composite slurry, and an electrode member (molded body) containing the binder and solid electrolyte particles is manufactured. The drying temperature in this step is preferably 90° C. or higher, more preferably 120° C. or higher, even more preferably 140° C. or higher, and particularly preferably 160° C. or higher, from the viewpoint of shortening the drying time and improving production efficiency. On the other hand, if the drying temperature becomes too high, the low-polarity nonaqueous solvent may suddenly boil, causing an increase in resistance due to uneven distribution of the granular material. From this viewpoint, the drying temperature is preferably 250° C. or lower, more preferably 220° C. or lower, even more preferably 200° C. or lower, and particularly preferably 170° C. or lower. The drying time is preferably 0.1 to 10 minutes.
[0042] (4) Temperature control of the mixture slurry In the manufacturing method disclosed herein, the temperature of the composite slurry is controlled at least until the molding step S20 is started so that the binder once dissolved in the solvent does not recrystallize. This prevents the composite slurry from gelling and maintains a low viscosity. As a result, molding of the composite slurry is facilitated and a decrease in the manufacturing efficiency of the electrode member is prevented. In addition, uneven distribution of the granular material can be prevented, thereby suppressing an increase in the battery resistance.
[0043] In addition, the specific temperature control of the composite slurry in the technology disclosed herein is not particularly limited as long as it can prevent the recrystallization of the binder until the start of the molding step S20. Hereinafter, the specific temperature control of the composite slurry will be described using two embodiments as examples.
[0044] (a) First embodiment In the first embodiment, the temperature of the composite slurry is controlled so as to satisfy the following formula (1) at least until the start of the molding step S20. T max ≦T m (1)
[0045] T in Equation (1) m is the "melting start temperature of the binder".m can be measured according to the following procedure. First, a test dispersion is prepared by dispersing the binder to be measured in a solvent to be used for the composite slurry. Then, a differential scanning calorimetry (DSC) is performed using a differential scanning calorimetry analyzer (TA Instruments Japan, DSC250) while gradually heating the test dispersion to obtain a DSC chart. The temperature at which an endothermic reaction is confirmed in the obtained DSC chart (endothermic reaction onset temperature) is defined as the "binder melting onset temperature T m ". It is to be noted that, although it is not intended to limit the technology disclosed herein, the melting start temperature T m The temperature is about 40°C to 60°C (for example, 45°C to 55°C).
[0046] On the other hand, T in Eq. (1) max is the "maximum temperature of the composite slurry." In this specification, the "maximum temperature T max " refers to the maximum temperature of the composite slurry from the start of the slurry preparation step S10 to the start of the molding step S20.
[0047] Here, the temperature of the composite slurry tends to rise due to shear heat during the kneading process even if no special heating process is performed. Therefore, if the slurry preparation step S10 is performed without controlling the temperature of the composite slurry, the maximum temperature T max is the binder melting temperature T m Exceeding (T max >T m The crystalline components of the binder dissolve in the low polarity nonaqueous solvent. Then, when the kneading process is completed, the temperature of the composite slurry drops, causing the binder that was once dissolved to recrystallize. In the conventional technology, it is assumed that the composite slurry gels through this mechanism. In contrast, in the manufacturing method according to the present embodiment, the composite slurry is cooled from the start of the slurry preparation step S10 until the start of the molding step S20, and the above T max ≦T mThis makes it possible to prevent the crystalline components of the binder from dissolving in the low-polarity nonaqueous solvent, so that recrystallization of the binder does not occur and gelation of the composite slurry can be prevented.
[0048] The means for controlling the temperature of the composite slurry is not particularly limited, and any conventionally known temperature adjustment means can be used without any particular limitation. For example, a jacket may be attached to a container that contains the composite slurry, and a cooling material (such as cold water) may be continuously supplied to the jacket while the slurry preparation step S10 is being carried out. This suppresses the temperature rise of the composite slurry due to shear heat during kneading, and the maximum temperature T max is the binder melting temperature T m It is possible to prevent the temperature of the composite slurry from exceeding the above range. In addition, when controlling the temperature of the composite slurry, it is preferable to continuously measure the temperature of the composite slurry and control the temperature and supply amount of the coolant according to the measurement result. This makes it possible to stably prevent gelation of the composite slurry. In addition, the means for controlling the temperature of the composite slurry is not limited to the above means. For example, the temperature of the composite slurry can also be controlled by a means for reducing the rotation speed in the kneading process to reduce shear heat.
[0049] In addition, the maximum temperature T max is the binder melting temperature T m It is preferable that the temperature is 5° C. or more lower than the maximum temperature T of the composite slurry. This can reliably prevent dissolution of the crystalline components of the binder and more suitably prevent gelation of the composite slurry. In addition, from the viewpoint of more reliably preventing dissolution of the binder, max is the binder melting temperature T m It is more preferable that the temperature is at least 10° C. lower than the above.
[0050] In order to prevent the mixture slurry from gelling, the maximum temperature T max The lower limit of the mixture slurry is not particularly limited. For example, the maximum temperature T max is the freezing point T of the low polarity non-aqueous solvent FAs an example, the maximum temperature T max may be -10°C or higher, may be -5°C or higher, or may be 0°C or higher. However, the maximum temperature T max When the maximum temperature T of the composite slurry exceeds a certain temperature, the molecules of the binder are loosened, and the binder can be easily dispersed in the slurry. This makes it possible to sufficiently improve the moldability of the composite slurry even in this embodiment in which the crystalline components of the binder are not dissolved in the solvent. From the viewpoint of the dispersibility of the binder, the maximum temperature T of the composite slurry is set to 100° C. max The lower limit is preferably 5° C. or higher, more preferably 10° C. or higher, and particularly preferably 15° C. or higher.
[0051] In addition, the electrode member manufactured according to this embodiment tends to have a lower endothermic reaction start temperature in a DSC chart obtained by differential scanning calorimetry than that of a conventional electrode member. Specifically, the binder that has been melted and recrystallized once has a higher endothermic reaction start temperature than before recrystallization. In other words, by obtaining a DSC chart of the electrode member and examining the endothermic reaction start temperature, it is possible to examine whether gelation due to recrystallization of the binder has been suppressed in the manufacturing process.
[0052] (b) Second embodiment In this embodiment, the temperature of the composite slurry is controlled so as to satisfy the following formulas (2) and (3) at least until the start of the molding step S20. T m <T max <T b (2) T min ≧T c (3)
[0053] As in the first embodiment described above, T in formula (2) of this embodiment m is the "temperature at which the binder begins to melt" and T max is the maximum temperature of the mixture slurry. bis the "boiling point of the low-polarity nonaqueous solvent". That is, the formula (2) in the second embodiment is the maximum temperature T max In this embodiment, as shown in the above formula (3), the minimum temperature T min is the recrystallization temperature T c That's all (T min ≧T c In other words, in this embodiment, the binder is dissolved in the solvent in the slurry preparation step, but the temperature of the composite slurry is maintained at a high level so that the binder does not recrystallize in the subsequent steps. Even when such temperature control is performed, gelation of the composite slurry due to recrystallization of the binder can be prevented.
[0054] In this specification, the recrystallization temperature T c The melting temperature T of the binder to be measured is measured after adding the binder to the solvent to be used for the composite slurry. m The test solution is prepared by heating the test solution to a temperature exceeding 100° C. to dissolve the binder. Then, while gradually cooling the test solution, differential scanning calorimetry is performed to obtain a DSC chart. The temperature at which an exothermic reaction is confirmed in the obtained DSC chart (exothermic reaction onset temperature) is defined as the "recrystallization temperature T c ". In addition, although this does not limit the technology disclosed herein, the recrystallization temperature T c The minimum temperature T of the composite slurry in this specification is about 25° C. to 45° C. (for example, 30° C. to 45° C.). min " refers to the lowest temperature of the composite slurry from the end of the slurry preparation step S10 to at least the start of the molding step S20. From the viewpoint of reliably preventing uneven distribution of granular particles, it is preferable that "refers to the lowest temperature of the composite slurry from the end of the slurry preparation step S10 to the start of the drying step S30."
[0055] In addition, the means for controlling the temperature of the composite slurry in this embodiment is not particularly limited, and conventionally known means can be adopted without particular limitation. For example, as in the first embodiment, a jacket may be attached to the container that contains the composite slurry, and a heating material (such as hot water) may be supplied to the jacket until the molding step S20 is started. This controls the temperature of the composite slurry so as to satisfy the above formulas (2) and (3), and prevents the composite slurry from gelling. Also, as in the first embodiment, it is preferable to continue measuring the temperature of the composite slurry and control the temperature and supply amount of the heating material according to the measurement result. This allows the composite slurry to be stably prevented from gelling.
[0056] In this embodiment, the minimum temperature T min is the recrystallization temperature T of the binder c It is preferable that the temperature is 5° C. or more higher than the minimum temperature T of the composite slurry. This can reliably prevent the dissolved binder from recrystallizing, and more suitably prevent the composite slurry from gelling. In addition, from the viewpoint of more reliably preventing the binder from recrystallizing, min is the recrystallization temperature T of the binder c It is more preferable that the temperature is at least 10° C. higher than the above.
[0057] (c) Summary of temperature control As described above, whether the means of the first or second embodiment described above is adopted, the crystalline components of the binder that have been dissolved once can be prevented from recrystallizing. This prevents gelation of the composite slurry and maintains a low viscosity, thereby preventing a decrease in the manufacturing efficiency of the electrode member. In addition, since uneven distribution of the granular material due to gelation can be prevented, an all-solid-state battery with low battery resistance can be stably manufactured.
[0058] In both the first and second embodiments described above, the temperature control for preventing the recrystallization of the binder is required to be performed at least until the molding step S20 is started. Specifically, in the manufacture of an electrode member for an all-solid-state battery, after the slurry preparation step S10 is completed, the composite slurry may be held for several hours (e.g., 8 hours or more) before the molding step S20 is performed. In order to prevent gelation of the composite slurry during such holding, it is necessary to continue the temperature control at least until the molding step S20 is started. Although the temperature control is relatively difficult, it is preferable to continue the temperature control of the composite slurry until before the drying step S30 is performed from the viewpoint of reliably preventing uneven distribution of the granular material. Such temperature control after the molding step S20 can be performed, for example, by adjusting the manufacturing environment (room temperature). Note that, since gelation of the slurry does not occur once the solvent is removed, the temperature control in the technology disclosed herein does not need to be performed after the drying step S30.
[0059] [Test example] Test examples relating to the technology disclosed herein will be described below. Note that the following test examples are not intended to limit the technology disclosed herein to those shown in the test examples.
[0060] <First Test> In this test, the binder melting temperature T m and the maximum temperature of the mixture slurry T max We produced 18 types of positive electrodes with different properties. Then, we constructed all-solid-state batteries (samples 1 to 18) using each positive electrode.
[0061] 1. Sample Preparation Cathode active material (LiNi 0.33 Mn 0.33 Co 0.33 O2), solid electrolyte particles (sulfide-based solid electrolyte), conductive material (VGCF), binder (PVdF-HFP), and low-polarity nonaqueous solvent (butyl butyrate: boiling point T b=170°C) was mixed to prepare a composite slurry for the positive electrode. The mixing ratio (weight ratio) of each material was set to positive electrode active material: solid electrolyte particles: conductive material: binder = 0.60: 0.30: 0.05: 0.05. In addition, in the preparation of the composite slurry, a kneading process was carried out for 0.2 to 3 minutes using an ultrasonic homogenizer. Then, after the prepared composite slurry was held for 6 hours, the composite slurry was applied to the surface of the positive electrode current collector foil (made of aluminum) using an applicator. Then, the applied composite slurry was dried to prepare a positive electrode.
[0062] A negative electrode composite slurry was prepared by mixing a negative electrode active material (natural graphite), solid electrolyte particles (sulfide-based solid electrolyte), conductive material (VGCF), binder (PVdF-HFP), and low-polarity nonaqueous solvent (butyl butyrate). The mixing ratio (weight ratio) of each material was set to negative electrode active material: solid electrolyte particles: conductive material: binder = 0.63: 0.26: 0.05: 0.06. In addition, the composite slurry was kneaded for 0.2 to 3 minutes using an ultrasonic homogenizer. Then, the composite slurry was applied to the surface of the negative electrode current collector foil (made of nickel) using an applicator, and then dried to prepare the negative electrode.
[0063] A composite slurry for the solid electrolyte layer was prepared by mixing solid electrolyte particles (sulfide-based solid electrolyte), a binder (PVdF-HFP), and a low-polarity non-aqueous solvent (butyl butyrate). The mixing ratio (weight ratio) of each material was set to solid electrolyte particles:binder = 0.96:0.04. In addition, an ultrasonic homogenizer was used to knead the composite slurry, and the kneading process was carried out for 0.2 to 3 minutes. Then, the composite slurry was applied to the surface of the substrate (aluminum foil) using an applicator and dried, and then the substrate was peeled off to prepare the solid electrolyte layer.
[0064] Next, the positive electrode, the solid electrolyte layer, and the negative electrode were laminated to form an electrode body. A positive electrode terminal (aluminum plate) was connected to the positive electrode current collector foil, and a negative electrode terminal (copper plate) was connected to the negative electrode current collector foil. Then, a pair of laminate films was placed facing each other with the electrode body sandwiched therebetween, and the outer periphery of the laminate film was welded to construct an all-solid-state battery.
[0065] In this test, the binder melting temperature T m and the maximum temperature of the mixture slurry T max The melting start temperature T of the binder of each sample was different for each of the samples 1 to 18. m and the maximum temperature of the mixture slurry T max The results are shown in Table 1. In this test, a thermometer was attached to the container containing the composite slurry, and the temperature of the composite slurry was continuously measured. The maximum temperature measured before the composite slurry was applied to the positive electrode current collector foil was defined as the "maximum temperature T max In addition, a DSC chart was obtained using the above procedure, and the endothermic reaction start temperature was regarded as the binder melting start temperature T m " was deemed to be the case.
[0066] 2.Evaluation Test (1) Measurement of viscosity increase rate of slurry Here, the viscosity (η0) of the composite slurry immediately after preparation was measured at room temperature (25°C) using an E-type viscometer with a shear rate of 40 / s. Next, the viscosity (η 6h ) was measured under the same conditions. Based on these measurement results, the viscosity increase rate (Δη = η 6h The calculation results are shown in Table 1 and Figure 4.
[0067] (2) Battery resistance measurement After the initial charge and discharge of each sample solid-state battery, a constant current discharge of 3C for 10 seconds was performed from SOC50% in a room temperature (25°C) environment. The voltage before discharge (V0) and the voltage after discharge (V 10sec ) and measure the change in voltage (ΔV=V0-V 10secThe battery resistance was calculated based on the above. The calculation results are shown in Table 1 and Figure 5.
[0068] [Table 1]
[0069] As shown in Table 1 and FIG. 4, in Samples 1 to 3, 7 to 10, and 13 to 17, gelation of the composite slurry did not occur, and the viscosity increase rate after 6 hours was suppressed to 140% or less. In addition, as shown in Table 1 and FIG. 5, in these samples in which gelation was prevented, the battery resistance was suppressed to 9Ω or less. From the above results, it can be seen that the maximum temperature T max is the binder melting temperature T m Below (T max ≦T m It was found that by controlling the temperature of the composite slurry so that the temperature becomes constant, it is possible to prevent the composite slurry from gelling and to construct a low-resistance all-solid-state battery.
[0070] <<Second Test>> In this test, the target of temperature control was changed to the negative electrode. That is, the binder melting start temperature T m and the maximum temperature of the mixture slurry T max We produced 18 types of negative electrodes with different properties, and constructed all-solid-state batteries (samples 19 to 36) using each negative electrode.
[0071] 1. Sample Preparation In this test, a positive electrode and a solid electrolyte layer were prepared in the same manner as in Sample 1 of the first test. m and the maximum temperature of the mixture slurry T max The melting temperature of the binder in each sample was different for samples 19 to 36. m and the maximum temperature of the mixture slurry T max is shown in Table 2.
[0072] 2.Evaluation Test The viscosity increase rate of the slurry and the battery resistance were measured according to the same procedure as in the first test. The measurement results of the viscosity increase rate of the slurry are shown in Table 2 and Figure 6. The measurement results of the battery resistance are shown in Table 2 and Figure 7.
[0073] [Table 2]
[0074] As shown in Table 2 and FIG. 6, in Samples 19 to 21, 25 to 28, and 31 to 35, gelation of the composite slurry did not occur, and the viscosity increase rate after 6 hours was suppressed to 140% or less. As shown in Table 2 and FIG. 7, in these samples, the battery resistance was suppressed to 9Ω or less. From these results, it can be seen that the T max ≦T m It has been found that gelation of the composite slurry can be prevented by controlling the temperature of the composite slurry so as to satisfy the above.
[0075] <<Third Test>> In this test, we investigated temperature control to prevent gelation of the composite slurry after the binder is dissolved in the solvent. Specifically, the recrystallization temperature T c and the minimum temperature of the mixture slurry T min Nine types of positive electrodes with different structures were manufactured, and each positive electrode was used to construct an all-solid-state battery (samples 37 to 48).
[0076] 1. Sample Preparation In this test, the solid electrolyte layer and the negative electrode were prepared in the same manner as in Sample 1 of the first test described above. max is the binder melting temperature T m The temperature of the composite slurry during kneading was controlled so that it exceeded the minimum temperature T , and a composite slurry in which the binder was dissolved in the solvent was prepared. The prepared composite slurry was then held at a predetermined temperature for six hours, and the composite slurry was applied to the surface of the positive electrode current collector foil using an applicator. In this test, the temperature of the composite slurry during holding was varied for each sample, and the minimum temperature Tmin In this test, the heat generation temperature (crystallization temperature T c ) were used for each sample. The minimum temperature of the mixture slurry, T min and crystallization temperature T c is shown in Table 3.
[0077] 2.Evaluation Test The viscosity increase rate of the slurry and the battery resistance were measured according to the same procedure as in the first test. The measurement results of the viscosity increase rate of the slurry are shown in Table 3 and Figure 8. The measurement results of the battery resistance are shown in Table 3 and Figure 9.
[0078] [Table 3]
[0079] As shown in Table 3 and FIG. 8, in Samples 38 to 42 and 46 to 48, gelation of the composite slurry did not occur, and the increase in viscosity after 6 hours was suppressed to 140% or less. As shown in Table 3 and FIG. 9, in these samples, the battery resistance was suppressed to 9Ω or less. From these experimental results, it can be seen that the maximum temperature T max is the binder melting temperature T m If the binder dissolves in the solvent at a temperature above the minimum temperature T min is the crystallization temperature T c It was found that gelation of the composite slurry can be prevented by controlling the temperature of the composite slurry so that it does not fall below this temperature.
[0080] Although the present invention has been described in detail above, the above-mentioned embodiments and examples are merely illustrative, and the invention disclosed herein includes various modifications and variations of the above-mentioned specific examples. [Explanation of symbols]
[0081] 1 All-solid-state battery 10 Electrode body 20 Exterior body 30 Positive terminal 40 Negative terminal 50 positive electrode 52. Positive electrode collector foil 54 Positive electrode composite layer 60 Negative electrode 62 Negative electrode collector foil 64 Negative electrode composite layer 70 Solid electrolyte layer
Claims
1. A method for manufacturing an electrode member constituting an electrode body of an all-solid-state battery, comprising the steps of: a slurry preparation step of preparing a composite slurry including at least a binder, solid electrolyte particles, and a low-polarity nonaqueous solvent; A forming step of forming the composite slurry into a desired shape; a drying step of removing the low polarity nonaqueous solvent from the composite slurry after molding to obtain a molded body; Equipped with The binder is a polymer having a VDF unit, The melting start temperature of the binder is T m The maximum temperature of the composite slurry is T max and controlling a temperature of the composite slurry so as to satisfy the following formula (1) at least until the molding step is started. T max ≦T m (1)
2. The method for manufacturing an electrode member according to claim 1 , wherein the binder is polyvinylidene fluoride (PVdF).
3. The method for manufacturing an electrode member according to claim 1, wherein the binder is PVdF-HFP, which is a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP).
4. The maximum temperature T of the composite slurry max is the melting start temperature T m The method for producing an electrode member according to any one of claims 1 to 3, wherein the temperature is 5°C or more lower than the temperature at which the electrode is heated.
5. the electrode member is a positive electrode or a negative electrode in which a composite layer containing the solid electrolyte particles and an electrode active material is formed on a surface of a current collector foil, The method for producing an electrode member according to any one of claims 1 to 4, wherein in the forming step, the composite slurry is applied to a surface of the current collector foil.
6. the electrode member is a solid electrolyte layer containing the solid electrolyte particles, The method for producing an electrode member according to any one of claims 1 to 4, wherein the composite slurry is applied to a surface of a foil-shaped base material in the forming step, and the foil-shaped base material is peeled off from the formed body obtained after the drying step.
Citation Information
Patent Citations
Electrode binder solution, electrode mixture, electrode structure, and battery
JP1997289023A
Electrode used for nonaqueous secondary battery and manufacture thereof
JP1998284052A
Secondary battery and manufacture thereof
JP1999086865A
Electrode mix, electrode structure using it, and nonaqueous electrochemical element
JP2004247180A
Manufacturing method of positive electrode mixture paste
JP2004247184A